Localization of a Retro Rectal Hydatid Cyst: A Rare Case Report (Bangladesh Journal of Infectious Diseases, 2023)
Cystic Echinococcosis (CE) is a worldwide zoonotic infection caused by the larval stage of  Echinococcus  granulosus. It has a widespread distribution in the human population of Tunisia.The liver hydatid cysts are the most commun abdominal site. However, other rare intra cavity location, can occur.   We report the case of 56 year old patient with surgical history for liver hydatid cyst. Ten years after surgery, he was presented with chronic abdominal pain and constipation. The imaging results were all in favor of a retro rectal hydatid cyst. A total resection of the hydatid cyst was executed good outcomes.Bangladesh Journal of Infectious Diseases, December 2023;10(2):101-103